2010
DOI: 10.5194/acp-10-11605-2010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and aerosol size distribution of the middle mountain range in the Nepal Himalayas during the 2009 pre-monsoon season

Abstract: Abstract. Aerosol particle number size distribution and chemical composition were measured at two low altitude sites, one urban and one relatively pristine valley, in Central Nepal during the 2009 pre-monsoon season (May-June). This is the first time that aerosol size distribution and chemical composition were measured simultaneously at lower elevations in the middle Himalayan region in Nepal. The aerosol size distribution was measured using a Scanning Mobility Particle Sizer (SMPS, 14-340 nm), and the chemica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Note that a partial coarse particulate influence over Hetauda was observed earlier in the AOD vs. AE relationship thus complementing the SSA variation. Compared to Hetauda, dust/coarse particle influence is found to weaken over Dhulikhel that shows a relatively flat spectrum suggesting a mix of local pollution aerosols from upslope transport as well as long-range transport of dust (Carrico et al, 2003;Shrestha et al, 2010). Unlike over Western IGP, SSA over Hetauda and Dhulikhel is generally lower at longer wavelengths (670-1020 nm) and less sensitive to variation in wavelength.…”
Section: Aerosol Single Scattering Albedomentioning
confidence: 90%
See 1 more Smart Citation
“…Note that a partial coarse particulate influence over Hetauda was observed earlier in the AOD vs. AE relationship thus complementing the SSA variation. Compared to Hetauda, dust/coarse particle influence is found to weaken over Dhulikhel that shows a relatively flat spectrum suggesting a mix of local pollution aerosols from upslope transport as well as long-range transport of dust (Carrico et al, 2003;Shrestha et al, 2010). Unlike over Western IGP, SSA over Hetauda and Dhulikhel is generally lower at longer wavelengths (670-1020 nm) and less sensitive to variation in wavelength.…”
Section: Aerosol Single Scattering Albedomentioning
confidence: 90%
“…Unlike over Western IGP, SSA over Hetauda and Dhulikhel is generally lower at longer wavelengths (670-1020 nm) and less sensitive to variation in wavelength. Chemical composition analysis carried out by Shrestha et al (2010) over Dhulikhel during the 2009 pre-monsoon period indicates organic carbon as a major fraction of the aerosol concentration with major sources of pollution in Kathmandu valley, in particular, and over the IGP, in general. Additionally, their chemical analysis found about 10 % contribution from elemental carbon in the total aerosol composition suggesting presence of significant absorbing aerosol concentration thus implying overall low spectral SSA (greater absorption) as reported here by AERONET over Dhulikhel.…”
Section: Aerosol Single Scattering Albedomentioning
confidence: 99%
“…During the last three decades, chemical studies of aerosols and snow in the Himalayan region have become of great interest in order to evaluate the impact of anthropogenic pollution over the high elevation mountain regions. Several studies have been reported from the northern slope of the Himalayas (Mayewski et al, 1983;Wake et al, 1994;Shrestha et al, 1997;Shrestha et al, 2000;Shrestha et al, 2002) and also from lower elevations in middle Himalayan region (Shrestha et al, 2010). Wake et al (1994) P. Hegde and K. Kawamura: Water-soluble organic carbon, dicarboxylic acids, ketocarboxylic acids studied aerosol samples collected from the southern slopes of the Himalayas to the northern margin of the Tibetan Plateau and reported high concentrations of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The aerosol pool is eventually scavenged by the formation of low-level clouds and fog, and washed out by rainfall similar to subregional scale forcing in the inner region of the Southern Appalachians investigated by [21,22]. Specifically, [26] showed that, in the presence of regional scale aerosol clouds and during dry periods, the mean volume aerosol concentration increased, and so did the aerosol mass concentrations in two different valleys of Central Nepal, the Marshyangdi and the Kathmandu, followed by rain-out. In addition, the topography of the region was found to play an important role in modulating the diurnal cycle of aerosol number concentration due to the diurnal cycle of katabatic and anabatic winds.…”
Section: Introductionmentioning
confidence: 87%